THE EVALUATION OF ACCESSIBILITY TO HOSPITAL INFRASTRUCTURE AT REGIONAL SCALE BY USING GIS SPACE ANALYSIS MODELS: THE NORTH-WEST REGION, ROMANIA - Şt. BILAŞCO; S. FILIP; P. COCEAN; D. PETREA; I. VESCAN; I. FODOREAN (Studia Universitatis Babeş-Bolyai: Geographia, 2015)
The Evaluation of Accessibility to Hospital Infrastructure at Regional Scale by Using GIS Space Analysis Models: the North-West Region, Romania. Easy access of the population to hospital infrastructure represents one of the main preoccupations of local and national authorities in the attempt to increase the degree of deliverance of quality medical services. The analysis of territorial distribution of various hospital categories- city, clinical, teaching, emergency hospitals- has revealed some areas of deficit in what regards the availability of various types of medical assistance. Identifying the areas of deficit from the point of view of accessibility to hospital infrastructure is carried out by means of a GIS model of space analysis (Cost Surface Modeling type) based on the calculation of access time from any location in the territory to the nearest hospital taking into consideration the vector databases (access ways, hospitals etc.), assignment (speed of motion on access ways, hospital type) and raster (access time).